Selective electrocatalytic hydrogenation using palladium nanoparticles electrochemically formed in layer-by-layer multilayer films - Villalba, Matias Ariel (2015)
Sequential adsorption of PdCl42- within weak polyelectrolyte layer-by-layer (LbL) self-assembled multilayer films with further electrochemical reduction to yield Pd0 nanoparticles (Pd-NPs) has been demonstrated. The electrocatalytic hydrogenation (ECH) of model molecules such as acetophenone and benzophenone on Pd-NPs of different sizes (6 to 35 nm) and bulk Pd crystal surface in hydroalcoholic acid solution has been investigated. Distribution of reaction products (secondary alcohols and alkanes) and faradaic yield was systematically investigated. While the polyelectrolyte multilayers act as nanoreactors by confining PdCl42- ions and preventing the formation of large crystals, their presence also alters the hydrogenation reaction and therefore heat treated surfaces showed only the effect of nanocrystal size on the reaction selectivity and faradaic yield. This journal is